The cult and cultivation of Haiku amongst Colombian writers (2022)
This article looks back at an intellectual craft and literary product that has yet to face the challenges posed by literary criticism. Today, in the midst of the twenty-first century, the cult and cultivation of haiku in Colombian writers today calls for properly literary horizons of understanding, since they are above all, like any other literary expression, words, language, communication and meaning; there are semantic fields and worldviews in them, just as there is epistemology, phenomenology and ideology. Being able to involve all this scaffolding of reflection and analysis will not deprive the haiku of Colombian writers of their link with the sensitive and intuitive experience gleaned from the Japanese tradition.